2014
DOI: 10.1007/s11095-014-1513-1
|View full text |Cite
|
Sign up to set email alerts
|

The Glucose-Lowering Potential of Exenatide Delivered Orally via Goblet Cell- Targeting Nanoparticles

Abstract: CSK peptide-modified chitosan nanoparticles could be a potential therapeutics for Type II diabetes patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
21
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(24 citation statements)
references
References 22 publications
3
21
0
Order By: Relevance
“…In vivo efficacy studies in diabetic rats demonstrated that insulin-loaded CSK-TMC-NPs had significantly higher hypoglycemic effect than achieved with unmodified TMC NPs [177]. Similar observations have been reported for Exendin-4-loaded CSK-TMC-NPs [178]. Although these studies demonstrated that goblet cell targeting ligands could improve oral absorption of insulin in rodents, more studies need to be carried out to critically evaluate the potential of goblet cell targeting.…”
Section: Recent Developments In Targeting Oral Nanoparticles To Spsupporting
confidence: 52%
“…In vivo efficacy studies in diabetic rats demonstrated that insulin-loaded CSK-TMC-NPs had significantly higher hypoglycemic effect than achieved with unmodified TMC NPs [177]. Similar observations have been reported for Exendin-4-loaded CSK-TMC-NPs [178]. Although these studies demonstrated that goblet cell targeting ligands could improve oral absorption of insulin in rodents, more studies need to be carried out to critically evaluate the potential of goblet cell targeting.…”
Section: Recent Developments In Targeting Oral Nanoparticles To Spsupporting
confidence: 52%
“…Prior to oral delivery of drug loaded NPs, 0.5 ml sodium bicarbonate solution was intragastrically administrated to neutralize the gastric acid [39,40]. Then the animals were administered by oral gavage with TNPs (50.0 IU/kg of insulin), P-T-NPs (50.0 IU/kg of insulin), insulin solution (50.0 IU/kg), or by subcutaneous injection (SC) with insulin solution (5.0 IU/kg).…”
Section: In Vivo Pharmacological and Pharmacokinetic Studiesmentioning
confidence: 99%
“…For permeability studies, a mixture of Caco-2 and HT29-MTX cells are seeded on semi-permeable polycarbonate Transwell filter inserts (Costar Transwell, Millipore Corp., Bedford, MA, USA) [ 8 , 37 , 58 ]. Predetermined cell numbers of Caco-2 and HT29-MTX cells are mixed prior to seeding to yield a specific ratio of Caco-2 to HT29-MTX cells.…”
Section: Developments Of In Vitro Methodsmentioning
confidence: 99%
“…Over the last few decades, the application of nanoparticles has been investigated for different routes of drug administration, which has opened up new possibilities for facing the shortcomings of current conventional dosage systems [ 5 ]. Although there have been tremendous innovations in different drug delivery systems, the oral route is still the most widespread and popular drug administration method by virtue of its convenience, low cost and high patient compliance compared with alternative routes [ 6 , 7 , 8 ]. However, the vulnerability of many drugs to the harsh conditions of the gastrointestinal (GI) tract and the possibility of chemical and enzymatic degradation results in poor therapeutic efficacy of many orally administered drugs [ 9 ].…”
Section: Introductionmentioning
confidence: 99%